Enhancing Students’ Financial Literacy through Sharia-Based Financial Management Training - Ayyu Ainin Mustafidah; Putri Kamilatul Rohmi; Rachma Dini Fitria; Novita Nurul Islami; Putri Catur Ayu Lestari (Universitas Lambung Mangkurat, 2026)
Despite increasing attention to financial literacy, limited contextual and Sharia-based interventions exist in pesantren settings. Therefore, this community service program aims to enhance students’ financial literacy through Sharia-based financial management training at the Ar Roudhoh Foundation, Jember. The program is motivated by the low level of students’ ability to manage personal finances and to support pesantren-based entrepreneurial activities. The method employed is Participatory Action Research (PAR), involving students, foundation administrators, and teachers (ustadz/ustadzah) in the planning, implementation, and evaluation stages. The training was conducted through interactive lectures, group discussions, pesantren-contextual case studies, simulations of budgeting, financial record-keeping, and savings planning based on Sharia principles, as well as the use of daily and weekly financial control sheets. Service evaluation was systematically designed to measure both learning outcomes and program effectiveness. The evaluation process consisted of quantitative and qualitative approaches, including pretest and posttest instruments to assess changes in financial literacy levels, structured observation sheets to evaluate participants’ practical financial management skills during simulations, and participant satisfaction questionnaires to measure the relevance, clarity, usefulness, and applicability of the training materials in daily life. Pretest results indicated that 80% of students were in the low to moderate financial literacy category, with mastery levels ranging from 53% to 67%. After the training, posttest results showed a significant improvement, with 92% of students achieving a high mastery category (83%–100%). Improvements were observed in budgeting skills, financial record-keeping, understanding of Sharia financial principles, and savings awareness. Participant evaluations revealed that the training materials were easy to understand, relevant to students’ needs, and supported by effective methods and media. Overall, Sharia-based financial management training has proven effective in improving students’ financial literacy and fostering more disciplined financial behavior in accordance with Islamic values, thereby potentially supporting the sustainable economic independence of pesantren.